Citation Count Analysis of Behavioral Science Journals in Influential Management Literature - Durand, Douglas E. (Academy of Management Journal, 1974)
The article looks at a survey which examined the influence of behavioral science journals on academicians and personnel managers in the U.S. A survey of academicians and practitioners was conducted first to determine which journals were most influential in the field of management. Researchers analyzed the number of bibliographical references to anthropological, psychological, and sociological journals within the management literature. The author concludes that academic and industrial respondents are influenced by many of the same journals.